2006
DOI: 10.1038/sj.bjp.0706788
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine reduces the organ injury and dysfunction in rodent models of Gram‐negative and Gram‐positive shock

Abstract: Lysophosphatidylcholine (LPC) modulates the inflammatory response and reduces mortality in animal models of sepsis. Here, we investigate the effects of LPC from synthetic (sLPC) and natural, soy bean derived LPC, (nLPC) sources on the organ injury/dysfunction caused by systemic administration of lipopolysaccharide (LPS) or peptidoglycan (PepG) and lipoteichoic acid (LTA). Rats were subjected to (i) endotoxaemia (LPS 6 mg kg–1 i.v.) and treated with sLPC (1–100 mg kg−1), (ii) endotoxaemia and treated with nLPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…This is recently supported by data suggesting that LPC is a death effector for lipoapoptosis of hepatocytes [18]. Paradoxically, some reports proposed protective functions for LPC in rodent models of sepsis [37,54]. This is also in accordance with our data showing that LPC at low concentrations can be partially protective against TNFa/CHX-induced apoptosis in CL48 cells.…”
Section: Discussionsupporting
confidence: 94%
“…This is recently supported by data suggesting that LPC is a death effector for lipoapoptosis of hepatocytes [18]. Paradoxically, some reports proposed protective functions for LPC in rodent models of sepsis [37,54]. This is also in accordance with our data showing that LPC at low concentrations can be partially protective against TNFa/CHX-induced apoptosis in CL48 cells.…”
Section: Discussionsupporting
confidence: 94%
“…We found that LPS injection (50 mg/kg) induced a consistent and significant increase in bioluminescent signals in the liver (Fig. 2a), which is a major target of LPS-induced septic shock [13]. No significant or consistent increase in bioluminescence was found in the other organs, such as the spleen, the kidneys, the lung, and the thymuses, following LPS injection.…”
Section: Resultsmentioning
confidence: 84%
“…Functional analysis of the mmp-9 promoter transgene MMP-9 gene expression is regulated by a number of different stimuli in different cell types, most notably by LPS in liver and kidney tissues [11][12][13]. To determine whether our transgene model may be used to assess the activation of the mmp-9 promoter by inflammatory mediators using bioluminescence imaging, we injected Tg and control mice with LPS.…”
Section: Resultsmentioning
confidence: 99%
“…LPC administration inhibited LPS-or cecal ligation and puncture (CLP)-induced increase in plasma HMGB1 levels in mice (Chen et al, 2005). Furthermore, LPC administration inhibited LPS-or peptidoglycan/lipoteichoic acid-induced multiple organ damage in rats (Murch et al, 2006).…”
Section: In Vivo Immuno-modulatory Actions Of Lpcmentioning
confidence: 99%